2007
DOI: 10.1111/j.1540-8167.2007.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of AF Recurrence After Pulmonary Vein Isolation by Eliminating ATP‐Induced Transient Venous Re‐Conduction

Abstract: The use of additional RF applications to eliminate transient PV reconnection induced by ATP injection led to a reduction of AF recurrence after PVI, most likely due to the minimization of the subsequent PV reconnection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
130
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 18 publications
1
130
2
1
Order By: Relevance
“…[8][9][10] However, these studies were retrospective and single-center, and the period during which the AF ablation was performed differed between them. Therefore, rapidly changing procedural techniques and increasing operator experience should have influenced the results of these noncontemporaneous studies.…”
Section: Adenosine Test At the Index Ablation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10] However, these studies were retrospective and single-center, and the period during which the AF ablation was performed differed between them. Therefore, rapidly changing procedural techniques and increasing operator experience should have influenced the results of these noncontemporaneous studies.…”
Section: Adenosine Test At the Index Ablation Proceduresmentioning
confidence: 99%
“…[6][7][8][9][10] Datino et al 19 elegantly showed that conduction recovery was related to adenosine-induced hyperpolarization of the PVs via an increase in the inward rectifier potassium current I Kado in a canine preparation. Hyperpolarization facilitated the closure of the inactivated sodium channels, making them available for activation, and resulted in resumed conduction in tissue where reversible thermal heating had occurred.…”
Section: Adenosine Test At the Index Ablation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have suggested that ablation guided by adenosine triphosphate (ATP)/adenosine administration can reduce AF recurrences at 1 year by 32-50 % (relative risk reduction). [53][54][55][56][57] Despite a lower incidence of DC (13-40 %), a similar effect has been suggested after cryoablation of the PV. 58,59 The recently-published randomised Adenosine Following Pulmonary Vein Isolation to Target Dormant Conduction Elimination (ADVICE) study was the first to prospectively evaluate the impact of adenosine testing on clinical outcomes after AF ablation.…”
Section: Clinical Valuementioning
confidence: 58%